Ambulatory oxygen for treatment of exertional hypoxaemia in pulmonary fibrosis (PFOX trial): a randomised controlled trial. Issue 12 (13th December 2020) - Holland, Anne E; Corte, Tamera; Chambers, Daniel C; Palmer, Andrew J; Ekström, Magnus Per; Glaspole, Ian; Goh, Nicole S L; Hepworth, Graham; Khor, Yet H; Hoffman, Mariana; Vlahos, Ross; Sköld, Magnus; et al.
Abstract : Introduction: Interstitial lung diseases are characterised by scarring of lung tissue that leads to reduced transfer of oxygen into the blood, decreased exercise capacity and premature death. Ambulatory oxygen therapy may be used to treat exertional oxyhaemoglobin desaturation, but there is little evidence to support its efficacy and there is wide variation in clinical practice. This study aims to compare the clinical efficacy and cost-effectiveness of ambulatory oxygen versus ambulatory air in people with fibrotic interstitial lung disease and exertional desaturation. Methods and analysis: A randomised, controlled trial with blinding of participants, clinicians and researchers will be conducted at trial sites in Australia and Sweden. Eligible participants will be randomised 1:1 into two groups. Intervention participants will receive ambulatory oxygen therapy using a portable oxygen concentrator (POC) during daily activities and control participants will use an identical POC modified to deliver air. Outcomes will be assessed at baseline, 3 months and 6 months. The primary outcome is change in physical activity measured by number of steps per day using a physical activity monitor (StepWatch). Secondary outcomes are functional capacity (6-minute walk distance), health-related quality of life (St George Respiratory Questionnaire, EQ-5D-5L and King's Brief Interstitial Lung Disease Questionnaire), breathlessness (Dyspnoea-12), fatigue (Fatigue Severity Scale), anxiety and depression (Hospital Anxiety and Depression Scale), physical activity level (GENEActive), oxygen saturation in daily life, POC usage, and plasma markers of skeletal muscle metabolism, systematic inflammation and oxidative stress. A cost-effectiveness evaluation will also be undertaken. Ethics and dissemination: Ethical approval has been granted in Australia by Alfred Hospital Human Research Ethics Committee (HREC/18/Alfred/42) with governance approval at all Australian sites, and in Sweden (Lund Dnr: 2019-02963). The results will be published in peer-reviewed scientific journals, presented at conferences and disseminated to consumers in publications for lay audiences. Trial registration number: ClinicalTrials.gov Registry (NCT03737409 ).